Modeling, analysis and simulation of 3D Elastohydrodynamic revolute joints in multibody systems - Flores, Paulo (2015)
In this work, a methodology for dynamic analysis of rigid-flexible multibody systems with elastohydrodynamic (EHD) lubricated joints is presented. The EHD lubricated cylindrical joint is formulated by the Natural Coordinate Formulation (NCF) and the twenty-node hexahedral element of Absolute Nodal Coordinate Formulation (ANCF), being the lubricant pressure determined through the resolution of the Reynolds’ equation employing the finite difference method. The outcomes are validated with those obtained by using the commercial software ADINA. It is demonstrated that the bearing flexibility plays a significant role in the system responses, extends the lubricant distribution space and reduces the lubricant pressure.